Mental health tracker - Pan, Qiao Lin (2024)
The project title is called Mental Health Tracker. At the end of the project, delivered an application called “Mind Unveil”. The project seeks to create an application with a safety and effectiveness application that provides users with efficient and effective detection of their mental health status and identifies potential danger awareness. The software will provide all the necessary tools for a mental health tracker and contains some additional features. The aim of this project is to provide users with an attractive and simple application to improve the awareness of the users of mental health. Several functions are implemented in the application including a registration and login function that allows users to create an account through email or phone number. Besides, the function of chat between therapist and patient allows the patient to solve their problem when they need to. The function of journaling allows users to vent without fear. In addition, the test function allows users to conduct the questions and analyze their situation of mental health. As the number of people with a common mental health condition has not decreased but increased in recent years [10], this system will provide a free and easy-to-use platform for users to detect and track their mental health. It will have a better understanding of the mental health tracker after reviewing some of the existing similar systems.